Water-soluble copolyesters
By developing water-soluble copolyesters based on terephthalic acid, isophthalic acid and aliphatic diols, the problems of insufficient bonding strength and poor solvent resistance during the printing process of existing water-based coatings are solved, and the problem of low temperatures is achieved Water-soluble copolyester with efficient dissolution and good performance, suitable for flexible packaging and advanced packaging materials.
Patent Information
- Application Number
- CN202480002819.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2024-02-16
- Publication Date
- 2025-01-10
AI Technical Summary
In the printing process, existing water-based coatings have problems such as insufficient bonding strength and poor solvent resistance, especially when the molecular weight decreases after long-term storage, resulting in deterioration in performance.
Developed a water-soluble copolyester based on terephthalic acid, isophthalic acid and aliphatic glycol with excellent solubility and surface tension properties for the preparation of adhesives that are efficiently dissolved at low temperatures, capable of Maintain properties in hot water and are used to form films or coatings with good scratch resistance and solvent resistance.
Achieve efficient dissolution of water-soluble copolyester at low temperatures, improves bond strength and ink adhesion, improves image quality and metal adhesion, is suitable for flexible packaging and pasteurized/cookable liquid packaging, providing Better industrial application performance.
Smart Images

Figure BDA0005161872030000061 
Figure BDA0005161872030000071 
Figure BDA0005161872030000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of water-soluble copolyesters. In particular, the present invention relates to a water-soluble copolyester having excellent solubility in hot water at low temperatures. It can be used as an adhesive based on its high glass transition temperature (Tg) and its better surface tension properties. Films or coatings prepared with the copolyesters of the present invention can be used to form topcoats, showing good scratch resistance and solvent resistance, as well as improved ink adhesion, improved metal bond strength and image quality. These features make the copolyesters of the present invention a dedicated grade for flexible packaging, especially pasteurizable / retortable liquid packaging. Background Art
[0002] Waterborne coating compositions of thermoplastic resin coatings (clear coatings) in the form of emulsions, such as thermoplastic (meth) acrylic or (meth) acrylic-styrene copolymers, are well known in the printing industry. In today's world, where climate change and its prevention are one of the sustainable development goals of the United Nations, it is important to limit the use of organic solvents and to prepare products that can use water as a solvent and can be used for various industrial purposes.
[0003] For example, referring to Japanese Patent Laid-Open No. 9-296100, an aqueous dispersion of a polyester resin obtained by dispersing a polyester resin having an acid value of 10-40 mg KOH / g and a weight average molecular weight of 9,000 or more in an aqueous medium is disclosed, and it is described that a coating film excellent in properties such as processability and solvent resistance can be prepared using this aqueous dispersion.
[0004] Similarly, referring further to US Pat. No. 5,384,160, a method is provided for depositing an aqueous coating composition onto an inked layer or an uninked surface during a printing process.
[0005] Referring again to U.S. Pat. No. 6,818,699, a polyester resin aqueous dispersion is provided, which can be used as a coating agent for various substrates and can form a high-quality polyester resin coating film having high adhesive strength, but if the dispersion is stored for a long time, the molecular weight of the polyester resin tends to decrease. Therefore, the problem of performance degradation may arise.
[0006] Therefore, there is a continuing need in the art for water-soluble copolyesters having improved properties and useful in a variety of industries. Summary of the invention
[0007] The object of the present invention is to develop a water-soluble copolyester having improved surface tension and adhesion.
[0008] Another object of the present invention is to develop a water-soluble copolyester based on terephthalic acid, isophthalic acid and aliphatic diols.
[0009] Another object of the present invention is to provide a method for preparing a water-soluble copolyester, which can be produced in the form of granules, flakes, powder or liquid.
[0010] Another object of the present invention is to provide a water-soluble copolyester having excellent solubility in hot water at low temperatures, which can be used as an adhesive and has better surface tension properties.
[0011] Another object of the present invention is to provide water soluble copolyester films or coatings that can be used to form topcoats that exhibit good coating compositions.
[0012] Yet another object of the present invention is to provide a water-soluble copolyester that can be used as a coating to improve one or more than one surface property of a polyester film. The improved surface property can be selected from, but not limited to, improved surface tension, adhesion, printing, metallization properties and / or gloss of the film.
[0013] Still another object of the present invention is to provide a water-soluble copolyester which can be directly used as a coating by dissolving in water without using any other organic or inorganic solvent.
[0014] Another object of the present invention is to provide a water-soluble copolyester that can be used to form a topcoat that exhibits good scratch and solvent resistance, as well as improved ink adhesion and image quality.
[0015] Another object of the present invention is to provide a water-soluble copolyester having increased bonding strength and improved dyne value, thereby resulting in effective printing and the printed matter is not rubbed off.
[0016] The copolyester of the present invention has improved surface tension, adhesion, adhesive strength, dyne value, resistance and solubility in water, making it widely used in the packaging field. DETAILED DESCRIPTION
[0017] Definition of terms
[0018] For convenience, certain terms used in the specification, examples and appended claims are collected here before further describing the present invention. These definitions should be read in light of the remainder of this disclosure and as understood by those skilled in the art. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art.
[0019] The articles "a," "an," and "the" are used to refer to one or to more than one (ie, to at least one) of the grammatical object of the article.
[0020] Throughout the specification, unless the context requires otherwise, the word "comprise", and variations such as "comprises" and "comprising", will be understood to imply the inclusion of stated elements or steps or groups of elements or steps but not the exclusion of any other elements or steps or groups of elements or steps.
[0021] The term "including" is used to mean "including, but not limited to." "Including" and "including, but not limited to" are used interchangeably.
[0022] The term "polyester" generally refers to the esterification or reaction product between a polybasic organic acid and a polyol. The present invention is particularly directed to a class of polyesters referred to herein as polyethylene terephthalate, wherein terephthalic acid is used as the polybasic organic acid, and particularly to PET, but it should be understood that the present invention is by no means limited to PET.
[0023] It covers all polyesters, namely PET, PBT, PTT and their related copolyester blends and alloys.
[0024] The term "polyester resin" refers to a polyester having a structure obtained by polycondensation of a dicarboxylic acid compound and a residue, such as polycondensation of a sulfonated terminal hydroxy ester and a sulfonated terminal carboxyl ester with a dihydroxy compound, polycondensation of a hydroxycarboxylic acid compound, or polycondensation of the above three compounds.
[0025] Ratio, concentration, amount and other numerical data are presented in range form in this article.It should be understood that the use of this range form is only for convenience and simplicity, and should be flexibly interpreted as not only comprising the numerical value clearly listed as the limit of the range, but also comprising all single numerical values or sub-ranges covered in the range, as each numerical value and sub-range are clearly listed.For example, 5 to 40 mol% should be interpreted as not only comprising the limit of 5 to 40 mol% clearly listed, but also comprising sub-ranges, such as 10 mol% to 30 mol%, 7 mol% to 25 mol%, etc., and a single amount in a specified range, comprising fractional amounts, such as 15.5 mol%, 29.1 mol% and 12.9 mol%.
[0026] The use of the expression "at least" or "at least one" implies the use of one or more elements or ingredients or amounts, as such use may be used in embodiments of the present disclosure to achieve one or more desired objectives or results.
[0027] Any discussion of documents, acts, materials, devices, articles or the like contained in this specification is solely for the purpose of providing a context for the present disclosure. It should not be taken as an admission that any or all of these matters form part of the prior art base or were common general knowledge in the field relevant to the present invention as it existed anywhere before the priority date of this application.
[0028] Although considerable emphasis has been placed on the specific features of the present disclosure herein, it should be understood that various modifications may be made and many changes may be made in the preferred embodiments without departing from the principles of the present disclosure. These and other modifications in the nature of the present disclosure or the preferred embodiments will be apparent to those skilled in the art from the disclosure herein, whereby it will be clearly understood that the foregoing descriptive content is to be construed as merely illustrative of the present disclosure and not limiting.
[0029] The water-soluble copolyester precursor of the present invention comprises:
[0030] a. at least one dicarboxylic acid or an ester thereof;
[0031] b. at least one diol;
[0032] c. At least dimethyl sulfonate isophthalate (DMSIP) or / sulfonate isophthalic acid (SIPA) 8-20 wt%.
[0033] Water-soluble copolyesters based on dicarboxylic acids, wherein the dicarboxylic acids are selected from the group consisting of aromatic and / or aliphatic acids, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 3,4′-diphenyl ether dicarboxylic acid, hexahydrophthalic acid, 2,7-naphthalene dicarboxylic acid, phthalic acid, 4,4′-methylene bis(benzoic acid), oxalic acid, malonic acid, succinic acid, methylsuccinic acid, glutaric acid, adipic acid, 3-methyladipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,11-undecanedioic acid, 1,10-decane dicarboxylic acid, undecanedioic acid, 1,12-dodecane dicarboxylic acid, hexadecanedioic acid, docosane dicarboxylic acid, tetracosane dicarboxylic acid, dimer acid, 1,4-cyclohexane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, 1,1-cyclohexane diacetic acid, fumaric acid, maleic acid, and hexahydrophthalic acid.
[0034] A diol is a compound containing two hydroxyl groups (-OH groups). Aliphatic diols are also referred to as diols. The terms diol or aliphatic diol are used interchangeably in the present invention. The diol of the present invention is selected from the group consisting of monoethylene glycol (MEG), diethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, dimer glycol, (cis, trans) 1,4-cyclohexanedimethanol, di(ethylene glycol), tri(ethylene glycol), poly(ethylene ether) glycol, poly(tetramethylene ether) glycol, branched glycol, hexanediol, or a combination thereof or a derivative thereof.
[0035] A water-soluble copolyester based on terephthalic acid, isophthalic acid and aliphatic diols is developed, wherein the molar ratio of terephthalic acid is at least 80 to 90 mol%, isophthalic acid is at least 10 to 20 mol%, and the aliphatic diol content is at least 80 to 75 mol% of monoethylene glycol, 20 to 25 mol% of 1,6-hexanediol, and optionally additional diols selected from the group consisting of up to 20 mol% of diethylene glycol, up to 25 mol% of 2-methyl-1,3-propanediol, 20 to 30 mol% of neopentyl glycol and mixtures thereof, based on the total acid amount, to constitute 100 mol% of the diol amount.
[0036] A water soluble copolyester wherein the ratio of DIMSIP / SIPA may vary from 0 to 20 wt% or 0 to 18 wt% trimellitic anhydride.
[0037] A water-soluble copolyester consisting of at least 20 to 25 mol% of 1,6-hexanediol based on diol content, wherein the remaining diol portion includes said ethylene glycol.
[0038] A water-soluble copolyester wherein the intrinsic viscosity of the polymer is adjusted from 0.300 dl / g to 0.500 dl / g in melt polymerization.
[0039] Water-soluble copolyesters pelletized by underwater melt pelletizer or underwater strand pelletizer are produced in the form of flakes / granules with a melting point of 80–180°C and can be used as adhesives in the flexible packaging film industry.
[0040] A water-soluble copolyester wherein the polyester has a glass transition temperature greater than 45°C.
[0041] In one embodiment of the present invention, provided herein is a water-soluble copolyester as described herein, wherein the water-soluble copolyester has a melt flow index of less than 80 g / 10 min as measured at 265° C. according to ASTM D1238.
[0042] In one embodiment of the present invention, provided herein is a water-soluble copolyester as described herein, wherein the water-soluble copolyester has a flake / granule / powder / flake form.
[0043] Quality parameters
[0044] Intrinsic viscosity
[0045] The intrinsic viscosity (IV) is a measure of the molecular weight of a polymer and is measured using an Ubbelohde viscometer from a dilute solution. All intrinsic viscosities were measured in a 60:40 mixture of phenol and S-tetrachloroethane at a concentration of 0.5%. The flow time of the solvent and solution was checked in an IV water bath maintained at a temperature of about 25°C. Using the Billmeyer equation, IV, η, is obtained by measuring the relative viscosity ηr of a single polymer concentration:
[0046] IV=[η]=0.25[(RV-1)+3ln RV] / c
[0047] Where η is the intrinsic viscosity, RV is the relative viscosity; and c is the concentration of the polymer solution (in g / dL). The relative viscosity (RV) is obtained from the ratio between the flow time of the solution (t) and the flow time of the pure solvent mixture (t0).
[0048] RV = nrel = flow time of solution (t) / flow time of solvent (t0)
[0049] IV must be controlled so that the processability and final properties of the polymer remain within the desired range. Class "A" certified burettes are used for IV measurements to increase accuracy.
[0050] COOH terminal group:
[0051] The polymer was dissolved in a mixture of phenol and chloroform (50:50 w / v) under reflux. After cooling to room temperature, the COOH end groups were determined by titration of a 0.025 N benzyl KOH solution using bromophenol blue as an indicator. A blank test and a sample were run simultaneously, and the final endpoint was a color change from blue to yellow. The COOH groups were calculated based on the following calculation, and the results are expressed in COOH milliequivalents / kg. In the equation, TR is the volume of benzyl KOH consumed by the sample, N is the equivalent concentration of benzyl KOH, and the blank is the volume of benzyl KOH consumed by the sample solution.
[0052] [(TR-blank)×N×1000]=COOH end groups (meq / kg)
[0053] Color Value
[0054] Color parameters were measured with a Hunter Lab Ultrascan VIS instrument. D65 illuminant and 10° angle were used for color measurement. Inspection was performed using amorphous sheets in reflectance mode of the Hunter Color Scan. Generally, the changes measured are also visible to the eye. The color of the transparent amorphous sheets was classified using the Hunter Color (L / a / b) and CIE Color (L* / a* / b*) based on contrast color theory. This theory assumes that the receptors in the human eye perceive colors as the following pairs of opposites.
[0055] L / L* value: light versus dark, where low numbers (0–50) represent dark and high numbers (51–100) represent light.
[0056] a / a* value: red versus green, where positive numbers represent red and negative numbers represent green.
[0057] b / b* value: yellow to blue, where positive numbers represent yellow and negative numbers represent blue.
[0058] DSC analysis
[0059] Differential Scanning Calorimeter (DSC) is a thermal analyzer that can accurately and quickly determine the thermal behavior of polymers, such as glass transition temperature (Tg), crystallization exotherm peak temperature (Tch), peak endotherm temperature (Tm), heat of crystallization (ΔH), and heat of fusion for all materials. The thermal properties of all polymer samples were monitored using a Perkin-Elmer model Jade DSC with a heating and cooling rate of 10°C per minute. A nitrogen purge was used to prevent oxidative degradation.
[0060] DEG / EG / IPA content
[0061] To determine diethylene glycol (DEG), ethylene glycol (EG), isophthalic acid (IPA) and other comonomers, polymer samples were transesterified with methanol in an autoclave with zinc acetate as catalyst at 200 °C for 2.5 h.
[0062] During methanolysis, the polymer sample was depolymerized and the liquid was filtered through Whatman 42 filter paper. After filtration, 1 microliter of the liquid was injected into an Agilent gas chromatograph (GC) under controlled GC configuration. DEG / EG / IPA / BDO was calculated based on RT (retention time) using internal standard ISTD (tetraethylene glycol dimethyl ether) and the results are expressed in wt%.
[0063] Sodium Content
[0064] To determine the sodium content in a polymer sample by wet ashing, take 0.5 g of sample and add 10 mL of pure concentrated H2SO4 and 2 mL of concentrated HNO3. Heat to above 150°C for carbonization. Add a mixture of 5 mL of concentrated HNO3 and 7 mL of perchloric acid. Heat until the solution is transparent. Cool it and transfer it to a clean 100 mL standard flask and make up with double distilled water. This is the main solution. The sodium content of the mother solution is detected using a microprocessor flame photometer G-30.
[0065] Sodium content in polymer = reading x composition weight (g) / sample weight (g).
[0066] Optical density
[0067] Optical density is the process by which a substance transmits light or other electromagnetic radiation. The process of emission and absorption depends on the wavelength of the radiation and involves interactions between elementary particles such as electrons, atoms, ions, etc.
[0068] When the light beam interacts with the absorbing atoms, absorption occurs. It depends on the thickness of the sample and the concentration of the absorbing atoms.
[0069] It is often considered the same as absorbance. It is the logarithmic ratio of the radiation falling to the radiation transmitted through the material.
[0070] For a given wavelength, the expression for the transmittance of an optical element is:
[0071] log 10 (1 / T);
[0072] Where T is the transmittance.
[0073] Optical density measurement
[0074] The measurement is done at the maximum of the absorption spectrum, since this is where the absorption has the least chance of varying with wavelength. This measurement is a common method for quantifying various important parameters such as cell concentration, biomass production, etc.
[0075] Absorbance A = -log(I / I0)
[0076] in,
[0077] I is the intensity of light passing through the sample
[0078] I0 is the initial light intensity.
[0079] Optical density by spectrophotometer
[0080] The formula for the spectrophotometer is:
[0081] OD=A / L
[0082] in,
[0083] L = thickness of the sample.
[0084] In other words, if a sample has an OD greater than 3, this means that the detector will only measure 1 photon out of 1,000. This small amount of light is difficult to accurately detect above the background noise, even with the most sophisticated instrumentation. Therefore, measurements greater than 3 O.D. will have larger errors and will be less accurate than measurements taken at lower ODs. Therefore, it is always recommended to dilute samples >3.0 OD and then factor the dilution factor into the final measurement. This is also shown in the following graph, noting that the measurement is no longer linear at high concentrations corresponding to higher OD values.
[0085] Oxygen Transmission Rate
[0086] Oxygen transmission rate was measured in accordance with ASTM D 3985-05 using a MOCON Ox-Tran model 2 / 21 analyzer at 23°C, 0% relative humidity, 1 atm. The test sample was fixed so that it separated the two sides of the test chamber. One side was exposed to a nitrogen atmosphere, while the other side was exposed to an oxygen atmosphere. A coulometric sensor monitoring the outlet of the nitrogen side measured the amount of oxygen present. The test was completed when the concentration of oxygen in the nitrogen side atmosphere was constant. For the stretched sample, the film was first stretched using an Instron stretcher. The stretched film was then held on a metal frame to prevent the film from relaxing, and the film stack frame was subsequently placed in the chamber to measure the oxygen transmission rate.
[0087] Water vapor transmission rate
[0088] The water vapor transmission rate ("WVTR", expressed as grams of water vapor transmitted through the film per 100 square inches of film per day at a specified film thickness in mils, or g / 100 in) was measured in accordance with ASTM F1249-90 at 100°F (37.8°C) and 90% relative humidity using a MOCON permatran model 3 / 33. 2 / sky).
[0089] Example
[0090] Example 1: A 50-liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet, and a heat source was charged with 2.43 kg of ethylene glycol, 1.2 kg of 1,6-hexanediol, 6.08 kg of terephthalic acid, 1.0 kg of isophthalic acid, and 2.98 g of antimony trioxide (250 ppm as antimony). The esterification reaction was carried out at a temperature of 240-260°C and a pressure of up to 3.0 bar for 2-3 hours. After 90% esterification was completed, the reactor was depressurized and phosphoric acid was added. The prepolymer was transferred to a polycondensation reactor. A sulfonated hydroxyl-terminated ester, such as a sodium solution of bis(2-hydroxyethyl)-5-sulfoisophthalate, was added. The reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form particles. The intrinsic viscosity of the amorphous polymer was 0.409 dl / g and the yield of the product from the reactor was greater than 96% (yield).
[0091] The results of the tested and measured analytical parameters are summarized in Table 1.
[0092] Example 2: A 50 liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet and a heat source is charged with 2.33 kg of ethylene glycol, 1.5 kg of diethylene glycol, 0.45 kg of 2-methyl-1,3-propanediol, 1.2 kg of neopentyl glycol, 9.51 kg of terephthalic acid, 0.375 kg of isophthalic acid, 0.3 kg of succinic acid and 4.48 g of antimony trioxide (250 ppm as antimony). The esterification reaction is carried out at a temperature of 240-260°C and a pressure of up to 3.0 bar for 2-3 hours. After 90% of the esterification is complete, the reactor is depressurized and phosphoric acid is added. The prepolymer is transferred to a polycondensation reactor. A sulfonated hydroxyl-terminated ester, such as a solution of sodium bis(2-hydroxyethyl)-5-sulfoisophthalate, is added. The reaction mixture is kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form particles. The intrinsic viscosity of the amorphous polymer was 0.279 dl / g and the yield of the product from the reactor was greater than 97.3% (yield).
[0093] Example 3: A 50-liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet and a heat source was charged with 2.08 kg of ethylene glycol, 2.25 kg of 1,4-butanediol, 2.55 kg of neopentyl glycol, 7.75 kg of terephthalic acid, 1.8 kg of isophthalic acid and 4.48 g of antimony trioxide (250 ppm as antimony). The esterification reaction was carried out at a temperature of 240-260°C and a pressure of up to 1.5 bar for 2-3 hours. After 90% esterification was completed, the reactor was depressurized and phosphoric acid was added. The polycondensation reaction was carried out at a temperature of 270-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped and the polymer was cooled to 250°C, 2.7 kg of trimellitic anhydride was added and depolymerized under N2 pressure until the acid value was as high as 40 to 60 KOH mg / g. The molten polymer was then cooled to 90°C and discharged in a SS tray. The intrinsic viscosity of the amorphous polymer was 0.251 dl / g and the yield of the product from the reactor was greater than 98.1% (yield).
[0094] The results of the tested and measured analytical parameters are summarized in Table 1.
[0095] Example 4: A 200 liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet and a heat source is charged with 7.33 kg of ethylene glycol, 8.0 kg of diethylene glycol, 8.0 kg of 2-methyl-1,3-propanediol, 8.0 kg of neopentyl glycol, 49.97 kg of terephthalic acid, 2.0 kg of isophthalic acid, 1.6 kg of succinic acid and 23.91 g of antimony trioxide (250 ppm as antimony). The esterification reaction is carried out at a temperature of 240-260°C and a pressure of up to 3.0 bar for 2-3 hours. After 90% of the esterification is complete, the reactor is depressurized and phosphoric acid is added. The prepolymer is transferred to a polycondensation reactor. A sulfonated hydroxyl-terminated ester, such as a solution of sodium bis(2-hydroxyethyl)-5-sulfoisophthalate, is added. The reaction mixture is kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form particles. The intrinsic viscosity of the amorphous polymer was 0.316 dl / g and the yield of the product from the reactor was greater than 98% (yield).
[0096] The results of the tested and measured analytical parameters are summarized in Table 1.
[0097] Example 5: A 50-liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet, and a heat source was charged with 4.19 kg of ethylene glycol, 1.5 kg of 1,6-hexanediol, 9.72 kg of terephthalic acid, 1.5 kg of isophthalic acid, 4.48 g of antimony trioxide (250 ppm as antimony). The esterification reaction was carried out at a temperature of 240-260°C and a pressure of up to 3.0 bar for 2-3 hours. After 90% esterification was completed, the reactor was depressurized and phosphoric acid was added. The prepolymer was transferred to a polycondensation reactor. A sulfonated hydroxyl-terminated ester, such as a sodium solution of bis(2-hydroxyethyl)-5-sulfoisophthalate, was added. The reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 270-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form particles. The intrinsic viscosity of the amorphous polymer was 0.398 dl / g and the yield of the product from the reactor was greater than 98% (yield).
[0098] The results of the tested and measured analytical parameters are summarized in Table 1.
[0099] Example 6: A 200 liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet and a heat source was charged with 20.58 kg of ethylene glycol, 10.4 kg of 1,6-hexanediol, 51.22 kg of terephthalic acid, 8.0 kg of isophthalic acid and 23.91 g of antimony trioxide (250 ppm as antimony). The esterification reaction was carried out at a temperature of 240-260°C and a pressure of up to 3.0 bar for 2-3 hours. After 90% esterification was completed, the reactor was depressurized and phosphoric acid was added. The prepolymer was transferred to a polycondensation reactor. A sulfonated hydroxyl-terminated ester, such as a sodium solution of bis(2-hydroxyethyl)-5-sulfoisophthalate, was added. The reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form particles. The intrinsic viscosity of the amorphous polymer was 0.424 dl / g and the yield of the product from the reactor was greater than 98.5% (yield).
[0100] The results of the tested and measured analytical parameters are summarized in Table 1.
[0101] Example 7: The procedure of Example 5 was repeated except that 15.0 wt% of 1,6-hexanediol was used instead of 13%. The results are summarized in Table 1.
[0102] Example 8: A 200 liter volume reactor equipped with a mechanical stirrer, a packed reflux column, a nitrogen inlet and a heat source was charged with 18.12 kg of ethylene glycol, 13.6 kg of 1,6-hexanediol, 48.83 kg of terephthalic acid, 9.6 kg of isophthalic acid and 23.91 g of antimony trioxide (250 ppm as antimony). The esterification reaction was carried out at a temperature of 240-260°C and a pressure of up to 3.0 bar for 2-3 hours. After 90% esterification was completed, the reactor was depressurized and phosphoric acid was added. The prepolymer was transferred to a polycondensation reactor. A sulfonated hydroxyl-terminated ester, such as a sodium solution of bis(2-hydroxyethyl)-5-sulfoisophthalate, was added. The reaction mixture was kept for 10 minutes for mixing. The polycondensation reaction was carried out at a temperature of 280-290°C and a pressure of less than 0.2 Torr. After reaching sufficient melt viscosity, the polymerization was stopped. The molten polymer was cooled in cold water and then chopped to form particles. The intrinsic viscosity of the amorphous polymer was 0.422 dl / g and the yield of the product from the reactor was greater than 98.5% (yield).
[0103] The results of the tested and measured analytical parameters are summarized in Table 1.
[0104] Preparation method of bis(2-hydroxyethyl)sodium 5-sulfoisophthalate monomer
[0105] The bis(2-hydroxyethyl)sodium 5-sulfoisophthalate used herein was prepared separately as described in Japanese Patent Laid-Open No. 57-23627A. In a separate reactor, 45 kg of NaDMSIP and 135 kg of ethylene glycol (three times on NaDMSIP) were mixed to form a solution, to which 0.1 wt% sodium acetate (relative to NaDMSIP) was added, and the solution was stirred at a temperature of up to 185°C for 90 minutes. The by-product, methanol, was collected, and the solution was then kept at 200°C for one hour as it was to ensure complete conversion. The reaction mixture was cooled and filtered to obtain a solid, which was used as it was without any further purification.
[0106] Table 1: Results of analytical parameters tested for Examples 1-8
[0107]
[0108]
[0109] Coating chemicals and coating preparation
[0110] Embodiment 9:
[0111] Solution A: 161 g of DM water was added to a closed container at room temperature and heated to a temperature of 40°C. 15.8 g of isopropanol was added at 40°C and stirred continuously. The temperature was raised to 52°C. 15.8 g of resin (resin prepared in Example 1) was added. The batch temperature was raised from 52°C to 85°C in 40 minutes and the solution was stirred continuously. The temperature was maintained up to 85°C until the resin was completely dissolved. The reaction mixture was allowed to cool to a maximum of 30°C and coated on an A4 size film. The results are summarized in Table 2.
[0112] Embodiment 10:
[0113] Solution A: 161 g of DM water was added to a closed container at room temperature and heated to a temperature of 40°C. 15.8 g of isopropanol was added at 40°C and stirred continuously. The temperature was raised to 52°C. Then 15.8 g of resin (resin prepared in Example 2) was added to the reaction mixture. The batch temperature was raised from 52°C to 85°C within 40 minutes and the solution was stirred continuously. The temperature was maintained at 85°C until the resin was completely dissolved. The reaction mixture was allowed to cool to a maximum of 30°C. 2.0 g of ETB was added to the reaction mixture. The reaction mixture was stirred for 10 minutes and coated on an A4 size film. The results are summarized in Table 2.
[0114] Embodiment 11:
[0115] Solution A: 161 g of DM water at room temperature is added to a closed container and heated to a temperature of 40°C. 15.8 g of isopropanol and 2.0 ammonia solution are added at 40°C and stirred continuously. The temperature is raised to 52°C. Then 15.8 g of resin (resin prepared in Example 3) is added to the reaction mixture. The batch temperature is raised from 52°C to 85°C in 40 minutes and the solution is stirred continuously. The temperature is maintained at up to 85°C until the resin is completely dissolved. Allow to cool to a maximum of 30°C.
[0116] Solution B: 1.0 g of IPA and 2.0 g of Cymal 303 were added to a flask and stirred for 10 minutes. Solution B was mixed with Solution A and coated on an A4 size film. The results are summarized in Table 2.
[0117] Embodiment 12:
[0118] Solution A: 161 g of DM water at room temperature was added to a sealed container and heated to a temperature of 40°C. 15.8 g of isopropanol was added at 40°C and stirring was continued. The temperature was raised to 52°C and 15.8 g of resin (resin prepared in Example 3) was added. The batch temperature was raised from 52°C to 85°C within 40 minutes and stirring was continued until the resin was completely dissolved. The reaction mixture was allowed to cool to a maximum of 30°C. 4.0 g of ETB was added and stirred for 10 minutes.
[0119] Solution B: 1.0 g of IPA and 0.5 g of Cymal 303 were added to a flask and stirred for 10 minutes. Solution B was mixed with Solution A and coated on an A4 size film. The results are summarized in Table 2.
[0120] Embodiment 13:
[0121] Solution A: 161 g of DM water was added to a sealed container at room temperature and heated to a temperature of 40°C. 15.8 g of isopropanol was added at 40°C and stirred continuously. The temperature was raised to 52°C and 15.8 g of resin (resin prepared in Example 4) was added thereto. The batch temperature was raised from 52°C to 85°C within 40 minutes and stirred continuously until the resin was completely dissolved. The reaction mixture was allowed to cool to a maximum of 30°C. 3.5 g of ETB was added and stirred for 10 minutes.
[0122] Solution B: 1.5 g of IPA and 1.0 g of Cymal 303 were added to a flask and stirred for 10 minutes. Solution B was mixed with Solution A and coated on an A4 size film. The results are summarized in Table 2.
[0123] Embodiment 14:
[0124] Solution A: 161 g of DM water was added to a sealed container at room temperature and heated to a temperature of 40°C. 15.8 g of isopropanol was added at 40°C and stirred continuously. The temperature was raised to 52°C and 15.8 g of resin (resin prepared in Example 5) was added thereto. The batch temperature was raised from 52°C to 85°C within 40 minutes and stirred continuously until the resin was completely dissolved. The reaction mixture was allowed to cool to a maximum of 30°C. 4.0 g of ETB was added and stirred for 10 minutes.
[0125] Solution B: 2.0 g of IPA and 2.0 g of Cymal 303 were added to a flask and stirred for 10 minutes. Solution B was mixed with Solution A and coated on an A4 size film. The results are summarized in Table 2.
[0126] Embodiment 15:
[0127] Solution A: 161 g of DM water was added to a sealed container at room temperature and heated to a temperature of 40°C. 15.8 g of isopropanol was added at 40°C and stirred continuously. The temperature was raised to 52°C and 15.8 g of resin (resin prepared in Example 6) was added thereto. The batch temperature was raised from 52°C to 85°C within 40 minutes and stirred continuously until the resin was completely dissolved. The reaction mixture was allowed to cool to a maximum of 30°C. 8.0 g of ETB was added and stirred for 10 minutes.
[0128] Solution B: 2.5 g of IPA and 2.0 g of Cymal 303 were added to a flask and stirred for 10 minutes. Solution B was mixed with Solution A and coated on an A4 size film. The results are summarized in Table 2.
[0129] Embodiment 16:
[0130] Solution A: 161 g of DM water at room temperature is added to a sealed container and heated to a temperature of 40°C. 15.8 g of isopropyl alcohol is added at 40°C and stirred continuously. The temperature is raised to 52°C and 15.8 g of resin (resin prepared in Example 7) is added thereto. The batch temperature is raised from 52°C to 85°C in 40 minutes and stirred continuously. The temperature is maintained up to 85°C until the resin is completely dissolved. Allow to cool to a maximum of 30°C. 10.0 g of ETB is added and stirred for 10 minutes.
[0131] Solution B: 3.0 g of IPA and 2.5 g of Cymal 303 were added to a flask and stirred for 10 minutes. Solution B was mixed with Solution A and coated on an A4 size film. The results are summarized in Table 2.
[0132] After Examples 9 to 16 were coated onto aluminum at OD of 2.3 to 2.7, metal adhesion (metal to film), oxygen transmission rate, and water vapor transmission rate were tested. The results are summarized in Table 2.
[0133] Table 2: Chemical compositions of coatings and post-coating quality parameters tested for Examples 9-16
[0134]
[0135] It can be inferred from Table 2 that in Examples 9, 13, 15 and 16, the polymer is not soluble, and in Examples 9, 10, 12 and 13, the polymer has poor adhesive strength and barrier properties. In Examples 11 and 14, the polymer has very good solubility, passes the ink test, the dye test, and excellent adhesive strength and barrier properties.
Claims
1. A water-soluble copolyester precursor comprising: a. at least one dicarboxylic acid or an ester thereof; b. at least one diol; and c. At least one dimethyl sulfonate isophthalate (DMSIP) or sulfonate isophthalic acid (SIPA) having a weight percentage ranging from 0 to 20 wt% or 0 to 18 wt% of trimellitic anhydride.
2. The copolyester precursor of claim 1, wherein the dicarboxylic acid is selected from aromatic and / or aliphatic acids, consisting of terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 3,4′-diphenyl ether dicarboxylic acid, hexahydrophthalic acid, 2,7-naphthalene dicarboxylic acid, phthalic acid, 4,4′-methylenebis(benzoic acid), oxalic acid, malonic acid, succinic acid, methylsuccinic acid, glutaric acid, adipic acid, 3-methylhexanedicarboxylic acid, 1,2-dihydro- ... The invention relates to a group consisting of 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,1-cyclohexanediacetic acid, fumaric acid, maleic acid, and hexahydrophthalic acid.
3. The copolyester precursor of claim 1, wherein the diol is selected from the group consisting of monoethylene glycol (MEG), diethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, dimer glycol, (cis, trans) 1,4-cyclohexanedimethanol, di(ethylene glycol), tri(ethylene glycol), poly(ethylene ether) glycol, poly(tetramethylene ether) glycol, branched glycol, hexanediol, or combinations or derivatives thereof.
4. The copolyester precursor of claim 1, wherein the ratio of DIMSIP / SIPA can vary from 0 to 20 wt% or 0 to 18 wt% trimellitic anhydride.
5. The copolyester precursor of claim 1 or 2, wherein the dicarboxylic acid is terephthalic acid having 80 to 90 mol% based on the acid content.
6. The copolyester precursor of claim 1 or 2, wherein the dicarboxylic acid is isophthalic acid having 10 to 20 mol% based on the acid content.
7. The copolyester precursor of claim 1 or 3, wherein the diol is 20 to 25 mol% of 1,6-hexanediol based on diol content, and wherein the remaining diol portion includes the ethylene glycol.
8. The copolyester precursor of claim 1, wherein the water-soluble copolyester has a melting point of 80 to 180°C.
9. The copolyester precursor of claim 1, wherein the water-soluble copolyester has a glass transition temperature greater than 45°C.
10. The copolyester precursor of claim 1, wherein the water-soluble copolyester has a melt flow index of less than 80 g / 10 min as measured at 265°C according to ASTM D 1238.
11. The copolyester precursor of claim 1, wherein the water-soluble copolyester is in the form of flakes / granules / powder / sheets.
12. The copolyester precursor of claim 1, wherein in the water-soluble copolyester, the IV of the polymer can be adjusted from 0.300 dl / g to 0.500 dl / g in melt polymerization.
13. The copolyester precursor of claim 1, wherein the water-soluble copolyester has a minimum Dv (surface tension) value of 56 after film coating.
14. The copolyester precursor of claim 1, wherein an A4 size film coated with the resin passes an ink test and a dye hue test for measuring film coating efficiency after boiling for 1 / 2 half hour.
15. The copolyester precursor of claim 1, wherein the resin coated A4 size film is first coated with ink and dye and then boiled to pass the ink test and dye hue test for measuring film coating efficiency.
16. The copolyester precursor of claim 1, wherein the composition optionally comprises an additional diol selected from the group consisting of 0 to 20 mol% of diethylene glycol, 0 to 25 mol% of 2-methyl-1,3-propanediol, 0 to 30 mol% of neopentyl glycol based on diol content, wherein the remaining diol portion comprises the ethylene glycol.
17. A film comprising the water-soluble copolyester according to any one of claims 1 to 16.
Citation Information
Patent Citations
Preparation of modified polyester
JP1982023627A
Aqueous polyester resin dispersion and production thereof
JP1997296100A
Method of coating a surface
US5384160A
Aqueous dispersion of polyester resin, production method of the same, and aqueous coating composition
US6818699B2